Thorvald's cross : the Viking-age cross-slab 'Kirk Andreas MM 128' and its iconography - Steinforth, Dirk H., (Archaeopress Archaeology, 2022)
The 'Manx Crosses', Scandinavian-style gravestones from the Isle of Man, are a unique collection of stone monuments unequalled in the medieval Viking World. Focusing on one particular example, 'Thorvald's cross', this book collates all the available information and presents a new interpretation as to how to understand this remarkable monument.